Analysis of factors for the acceptance and use of technology for the design of digital services in Ecuador - Pintado, Pablo (2024)
The adoption of digital services depends on different factors related to the acceptance and use of technologies. Despite a variety of research on techniques and models for technology acceptance and use, scarce research explores the factors of acceptance and use of technologies depending on the digital service's economic activity and the user's demographic characteristics in the Ecuadorian context. This article presents and analyzes a conceptual framework of the factors of acceptance and use of digital services in the Ecuadorian context. Its main contribution is to serve as a guide identifying major factors that policy makers and software developers need to consider when planning and designing digital services in Ecuador, so to facilitate their usage and adoption.